2020
DOI: 10.3389/fcell.2020.00473
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Compaction Switches Stress Response Programs and Enhances Therapeutic Efficacy of Endometrial Mesenchymal Stem/Stromal Cells

Abstract: Mesenchymal stem cells are currently tested as a promising tool for the treatment of a wide range of human diseases. Enhanced therapeutic potential of spheroids formed from these cells has been proved in numerous studies, however, the fundamental basics of this effect are still being discussed. In this work, we showed that endometrial mesenchymal stem/stromal cells (eMSCs) assembled in spheroids possess a higher therapeutic efficacy compared to cells grown in monolayer in the treatment of the defects that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…In contrast, it has been reported that cultivation of human periodontal ligament fibroblasts, a cell type which is phenotypically indistinguishable from MSCs [ 95 ], in 3D methylcellulose hydrogels results in suppression of TNF-α-induced cellular senescence and an increase in proliferation and migration [ 96 ]. In an attempt to study the stress response in human endometrial MSCs cultivated as 3D spheroids in comparison to conventional 2D culture, Domnina and colleagues exposed cells cultivated under both conditions to heat shock and treatment with H 2 O 2 [ 97 ]. This study demonstrated that 2D monolayer MSCs developed premature senescence, while MSCs in 3D exhibited decreased viability without cell cycle arrest and other signs of senescence.…”
Section: Impact Of 3d Cell Culture On Bone Regeneration-relevant Propmentioning
confidence: 99%
“…In contrast, it has been reported that cultivation of human periodontal ligament fibroblasts, a cell type which is phenotypically indistinguishable from MSCs [ 95 ], in 3D methylcellulose hydrogels results in suppression of TNF-α-induced cellular senescence and an increase in proliferation and migration [ 96 ]. In an attempt to study the stress response in human endometrial MSCs cultivated as 3D spheroids in comparison to conventional 2D culture, Domnina and colleagues exposed cells cultivated under both conditions to heat shock and treatment with H 2 O 2 [ 97 ]. This study demonstrated that 2D monolayer MSCs developed premature senescence, while MSCs in 3D exhibited decreased viability without cell cycle arrest and other signs of senescence.…”
Section: Impact Of 3d Cell Culture On Bone Regeneration-relevant Propmentioning
confidence: 99%
“…4), EC50 of CF fragments = 0.8 mM, HeLa ; EC50 of 2D culture = 75 µM 39 , EC50 of CF fragment = 85 µM). This is because H 2 O 2 acts on all cells at once in 2D culture, while in 3D tissue, only cells on the tissue surface are affected by H 2 O 2 40 , suggesting that the EC50 is higher in 3D tissue. In 2D cultures, β-estradiol has been reported to have proliferative and trophic effects at low concentrations, but these effects are suppressed at high concentrations 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…As reported recently and also shown in our study, cardiac glycosides do not induce apoptosis in both hMESCs and their senescent partners 105 . Obviously, the high resistance of hMESCs to cardiac glycosides is provided by a highly expressed anti-apoptotic program in these cells 32,64,65,106,107 . Taken together, the above data suggest that the depletion of cellular K + is necessary event in cardiac glycoside-induced apoptosis; however, a separate apoptotic signal is required to kill a cell, which acts together with low cellular K + .…”
Section: Discussionmentioning
confidence: 99%